Validity of the activPAL3 activity monitor in people moderately affected by Multiple Sclerosis. (July 2017) - Coulter, E.H.; Miller, L.; McCorkell, S.; McGuire, C.; Algie, K.; Freeman, J.; Weller, B.; Mattison, P.G.; McConnachie, A.; Wu, O.; Paul, L.
Highlights: The criterion validity of the activPAL3 accelerometer in comparison to video observation was assessed in people with Multiple Sclerosis. The activPAL3 underestimated steps and walking duration in those with slow cadences of less than 38 steps/minute. The activPAL3 was accurate for measuring upright duration regardless of walking cadence. Abstract: Walking is the primary form of physical activity performed by people with Multiple Sclerosis (MS), therefore it is important to ensure the validity of tools employed to measure walking activity. The aim of this study was to assess the criterion validity of the activPAL3 activity monitor during overground walking in people with MS. Validity of the activPAL3 accelerometer was compared to video observation in 20 people moderately affected by MS. Participants walked 20–30 m twice along a straight quiet corridor at a comfortable speed. Inter-rater reliability of video observations was excellent (all intraclass correlations >0.99). The mean difference (activPAL3- mean of raters) was −4.70 ± 9.09, −4.55 s ± 10.76 and 1.11 s ± 1.11 for steps taken, walking duration and upright duration respectively. These differences represented 8.7%, 10.0% and 1.8% of the mean for each measure respectively. The activPAL3 tended to underestimate steps taken and walking duration in those who walked at cadences of ≤38 steps/min by 60% and 47%, respectively. The activPAL3 is valid for measuring walking activity in people moderately affected by MS. It is accurate for upright duration regardless of cadence. In participants with slow walking cadences, outcomes of steps taken and walking duration should be interpreted with caution.